2009
DOI: 10.1111/j.1463-1326.2009.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Three different premixed combinations of biphasic insulin aspart – comparison of the efficacy and safety in a randomized controlled clinical trial in subjects with type 2 diabetes

Abstract: Glycaemic control improved with BIAsp 50 t.i.d. without higher incidence of hypoglycaemia compared with BIAsp 30 b.i.d.; with BIAsp 70 t.i.d. lower PG levels from lunch to 02.00 hours, but more hypoglycaemic episodes were obtained compared with BIAsp 30 b.i.d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…In a 12-week randomized study of insulin-naive Chinese patients with type 2 diabetes, LM50 twice daily for 12 weeks was associated with better glycemic control (HbA1c 5.5 ± 1.4% vs 6.5 ± 1.5%, p < 0.05) and more rapid achievement of target blood glucose levels (12.6 ± 3.6 days vs 22.3 ± 4.7 days, p < 0.05) than LM25 twice daily, without an increase in hypoglycemic episodes [22]. Another randomized clinical trial found that mid-mix biphasic insulin aspartate (BIAsp) three times daily also improved glycemic control to a greater extent than low-mix BIAsp twice daily without a causing a higher incidence of hypoglycemia [23]. In contrast, an open-label randomized study found that switching to LM50 from LM25 in 302 patients with type 2 diabetes who had not achieved adequate glycemic control did not clearly produce an improvement in overall glycemic control in terms of endpoints similar to those used in the current study [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a 12-week randomized study of insulin-naive Chinese patients with type 2 diabetes, LM50 twice daily for 12 weeks was associated with better glycemic control (HbA1c 5.5 ± 1.4% vs 6.5 ± 1.5%, p < 0.05) and more rapid achievement of target blood glucose levels (12.6 ± 3.6 days vs 22.3 ± 4.7 days, p < 0.05) than LM25 twice daily, without an increase in hypoglycemic episodes [22]. Another randomized clinical trial found that mid-mix biphasic insulin aspartate (BIAsp) three times daily also improved glycemic control to a greater extent than low-mix BIAsp twice daily without a causing a higher incidence of hypoglycemia [23]. In contrast, an open-label randomized study found that switching to LM50 from LM25 in 302 patients with type 2 diabetes who had not achieved adequate glycemic control did not clearly produce an improvement in overall glycemic control in terms of endpoints similar to those used in the current study [24].…”
Section: Discussionmentioning
confidence: 99%
“…Tsukuda et al 4) reported that BG profile after thrice daily injections of BIAsp70 in patients with T2DM was close to that of healthy subjects. However, the majority of the papers that we referred 3,5,6) have demonstrated that use of BIAsp70 as pre-dinner insulin failed to control nighttime glycemia in some cases. They concluded that different combination of biphasic formulations, such as BIAsp70 before breakfast and lunch and BIAsp30 (30% rapid acting and 70% intermediateacting insulin) before dinner, could control glycemia in patients with unsatisfactory BG levels during nighttime and before breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear evidence that twice daily regimens using such premixed preparations in young children are less effective for glycemic control, but some evidence shows poorer glycemic control are appeared when it is used in adolescents 9) . Thrice daily injections of high ratio of Ra biphasic insulin analog, such as BIAsp70, have been reported it could replicate physiological bolus and basal pattern on MDI in adults with T2DM [4][5][6] . Tsukuda et al 4) reported that BG profile after thrice daily injections of BIAsp70 in patients with T2DM was close to that of healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chadha showed data from two recent studies demonstrating clear benefits of high ratio premixed insulins on postprandial glucose profile and overall metabolic control in people with type 2 diabetes. 51,52 Keynote Lecture: The Selfish Brain-Conflicting Interests Between Brain and Body Can Help to Explain Why Diets Often Fail Achim Peters, Luebeck, Germany…”
Section: Monitoring and Treatment Of Pphmentioning
confidence: 99%